Henoch–Schönlein Purpura (IgA Vasculitis) in Association with Thyrotoxicosis - Mojgan Sanjari; Mohammadreza Shakibi; Moeinadin Safavi (Case Reports in Endocrinology)
Graves’ disease is the most common cause of hyperthyroidism, which is characterized by thyroid antibodies and the following clinical manifestations: goiter, ophthalmopathy, and pretibial myxedema. On the other hand, Henoch–Schönlein purpura is an IgA-mediated small-vessel vasculitis. Review of the literature showed a relationship between propylthiouracil overdose and the following Henoch–Schönlein purpura (IgA vasculitis) as a side effect. The patient was a 31-year-old woman with a chief complaint of tremor and significant weight loss who contracted pruritic palpable purpura during her disease course. Then, she underwent the treatment of hyperthyroidism by methimazole which intensified her cutaneous lesions. The diagnosis of Henoch–Schönlein purpura (IgA vasculitis) was confirmed after skin biopsy. Finally, she was treated with colchicine, prednisolone, and radioiodine ablation, which caused her lesions to disappear. The temporal priority of pruritic palpable skin lesions to hyperthyroidism treatment with methimazole suggested that Henoch–Schönlein purpura (IgA vasculitis) was related to hyperthyroidism and was intensified by antithyroid agents in this patient.